KARAKT£RISASI SENYAWA AKTIF ANTI BAKTERI MINYAK ATSIRI BUNGA CENGKEH (Syzygium arimaticum) - Dede Sukandar; Nani Radiastuti; Khoeriyah Khoeriyah (Jurnal Kimia Terapan Indonesia, 2010)
Water distillation and purification of drought clove (Syzygium arimaticum) interest yields clove interest essential oils 6,5 % (v/w), rust colored ofchocolate, refractive index (25°C) 1,52874, specific mass (25°C) 1,0636 g/ml and condensation in ethanol 70% (1:2) limpid. Oil of clove haves the character of antibacterial to five test bacteriums ( B. subtilis, B. cereus, S. aureus, P. aeroginosa and E. coli). Result of analysis GCMS shows existence of eugenol compound (72,98%), kariaphilena (10,40%), a-humulena (1,04%) and acetate eugenol ( 15,58%). SpectraphotometerJKTI, VOL. 12, No.1, Juni 2010 analysis UV- Vis existence of absorption at Amaks 207,63 nm (ethanol) and 283,76 nm (eugenol). Analysis FTIR existence of bunch - OH (3543,39 em'), aliphatic C-H (1605,79 - 1766,90 em'), aromatic C=C ( 1433,60 - 1514,74 em'), C-Caril (1433,60-1514,74em-I) and cO (1268,44 em'). Keyword: Antibacterial, clove (Syzygium arimaticum) and essential oils.